Odpowiedzi

Najlepsza Odpowiedź!
2010-03-21T18:48:40+01:00
1.
an = n²-5n
0=n(n-5)
D:n∈N dodatnich
n=0
n-5=0
n=5
a₅=0

2.
5, 9, 2x-1

róznica jest stała
a₁=5
a₂=9
a₃=2x-1
r₁=a₂-a₁
r₂=a₃-a₂
r₁=r₂
a₂-a₁=a₃-a₂
9-5=2x-1-9
4=2x-10
14=2x
x=7

3.
3x+2, 7, -2
iloraz jest stały
a₁=3x+2
a₂=7
a₃=-2

q₁= a₂/a₁
q₂=a₃/a₂

q₁=q₂
a₂/a₁=a₃/a₂
7/3x+2=-2/7
49=-2(3x+2)
49=-6x-4
49+4=-6x
53=-6x
x=-8⅚

4.
an=(n-4)(n-7)
0>(n-4)(n-7)
n-4=0
n=4

n-7=0
n=7

n∈(4,7) sa ujemne

5.
a15=a₁+14r
a103=a₁+102
Sn=3n²+5n
a₁=S₁=3*1²+5*1=3+5=8
S₂=3*2²+5*1
S₂=12+5=17
S₂=a₁+a₂
a₂=S₂-a₁=17-8=9

r=a₂-a₁=9-8=1
a₁₅=a₁+14r=8+14*1=8+14=22
a₁₀₃=a₁+102r=8+102*1=8+102=110

6.
a3=6 i a5=54.
a3=a1*q²
a5=a1*q⁴

6=a1*q²
54=a1*q⁴

6/q²=a1
54=6/q²*q⁴

6/q²=a1
54=6/q²

6/q²=a1
54*q²=6

6/q²=a1
q²=1/9
q²=1/3
a1=6*9
a1=54
an=a1*q do potęgi n-1
an=54*1/3 do potęgi n-1

7.
a11=a1+12r

a3=-5
a8=5

a3=a1+2r
a8=a1+7r

-5=a1+2r
5=a1+7r

-5-2r=a1
5=-5-2r+7r

-5-2r=a1
5=-5+5r

-5-2r=a1
10=5r

-5-2r=a1
r=2

-5-2*2=a1
r=2

a1=-1
r=2
1 4 1